Protective role of circRNA CCND1 in ulcerative colitis via miR-142-5p/NCOA3 axis - Ping Xiang; Tingrui Ge; Jingyi Zhou; Yonggang Zhang (BMC Gastroenterology, 2023)
Abstract Background Increasing research indicates that circular RNAs (circRNAs) play critical roles in the development of ulcerative colitis (UC). This study aimed to determine the role of circRNA CCND1 in UC bio-progression, which has been shown to be downregulated in UC tissues. Methods Reverse transcription quantitative polymerase chain reaction was used to determine the levels of circRNA CCND1, miR-142-5p, and nuclear receptor coactivator-3 (NCOA3) in UC tissues and in lipopolysaccharide (LPS)-induced Caco-2 cells. Target sites of circRNA CCND1 and miR-142-5p were predicted using StarBase, and TargetScan to forecast potential linkage points of NCOA3 and miR-142-5p, which were confirmed by a double luciferase reporter-gene assay. Cell Counting Kit 8 and flow cytometry assays were performed to assess Caco-2 cell viability and apoptosis. TNF-α, IL-1β, IL-6, and IL-8 were detected using Enzyme-Linked Immunosorbent Assay kits. Results CircRNA CCND1 was downregulated in UC clinical samples and LPS-induced Caco-2 cells. In addition, circRNA CCND1 overexpression suppressed LPS-induced apoptosis and inflammatory responses in Caco-2 cells. Dual-luciferase reporter-gene assays showed that miR-142-5p could be linked to circRNA CCND1. Moreover, miR-142-5p was found to be highly expressed in UC, and its silencing inhibited LPS-stimulated Caco-2 cell apoptosis and inflammatory responses. Importantly, NCOA3 was found downstream of miR-142-5p. Overexpression of miR-142-5p reversed the inhibitory effect of circRNA CCND1-plasmid on LPS-stimulated Caco-2 cells, and the effects of miR-142-5p inhibitor were reversed by si-NCOA3. Conclusion CircRNA CCND1 is involved in UC development by dampening miR-142-5p function, and may represent a novel approach for treating UC patients.